2009
DOI: 10.1155/2009/812102
|View full text |Cite
|
Sign up to set email alerts
|

Maintained Smoking Cessation for 6 Months Equilibrates the Percentage of SputumCD8+Lymphocyte Cells with That of Nonsmokers

Abstract: Little is known about the longitudinal effects of smoking cessation on sputum inflammatory cells. We aimed to investigate the changes in sputum inflammatory cells and T-lymphocyte subpopulations after 6 and 12 months smoking cessation. Induced sputum was obtained from 68 healthy smokers before and after 6 months (n = 21) and 1 year (n = 14) smoking cessation and from ten healthy never-smokers. Inflammatory cells were identified by morphology and T-lymphocyte subpopulations by flow cytometry. Sputum macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
10
1
2
Order By: Relevance
“…After 6 months-cessation, the percentage of CD8 + T-cells increased in quitters and a ratio of CD4 + /CD8 + decreased [13]. As the major activity ofCD8 + T lymphocytes is the facilitation of the rapid resolution of acute viral infections, the lower percentage of CD8 + T-cells suggests that smokers may have a deficit in cell-mediated immunity in the lung and may explain the increased susceptibility of smokers for viral infections.…”
Section: Inflammation and Immune Changesmentioning
confidence: 99%
“…After 6 months-cessation, the percentage of CD8 + T-cells increased in quitters and a ratio of CD4 + /CD8 + decreased [13]. As the major activity ofCD8 + T lymphocytes is the facilitation of the rapid resolution of acute viral infections, the lower percentage of CD8 + T-cells suggests that smokers may have a deficit in cell-mediated immunity in the lung and may explain the increased susceptibility of smokers for viral infections.…”
Section: Inflammation and Immune Changesmentioning
confidence: 99%
“…Therefore, continued CS increases the susceptibility of COPD subjects to bacterial and/or viral infections (50). Although the mechanisms of CS-induced lung damage have not been fully elucidated, it has been proposed that early inflammatory responses are responsible for tissue damage (18,20). Studies have shown that CS may result in a localized reaction and sequestration of neutrophils via the release of toxic and chemotactic mediators in pulmonary microvasculature, further predisposing the lungs to inflammatory disease (18,20).…”
Section: Effects Of Tobacco On the Immune System In Copdmentioning
confidence: 99%
“…Although the mechanisms of CS-induced lung damage have not been fully elucidated, it has been proposed that early inflammatory responses are responsible for tissue damage (18,20). Studies have shown that CS may result in a localized reaction and sequestration of neutrophils via the release of toxic and chemotactic mediators in pulmonary microvasculature, further predisposing the lungs to inflammatory disease (18,20). For example, it has been found that the population of inflammatory cells recovered from bronchoalveolar lavage fluid (BALF) is higher in smokers compared with nonsmokers (34).…”
Section: Effects Of Tobacco On the Immune System In Copdmentioning
confidence: 99%
“…Domagala-Kulawik 61 reported that even after smoking cessation, many changes in the immune system (caused by tobacco) are still present. On the other hand, Bouloukaki et al 62 suggested that, there is an increase of CD8 + T-cells and a decrease of the CD4 + /CD8 + within 6 months after smoking cessation. Morozumi et al 46 state that it takes more than 8 weeks for levels of IL-1β, IL-8, TNF-α and VEGF Braz Oral Res., (São Paulo) 2012;26(Spec Iss 1): [25][26][27][28][29][30][31] to return to their normal values, and that the role (or function) of neutrophils is still not completely recovered after this period.…”
Section: Smoking Cessation and Periodontal Tissuesmentioning
confidence: 99%